Privacy preserving mobile forensic framework using role‐based access control and cryptography. (12th July 2022) - Hyder, Muhammad Faraz; Arshad, Saadia; Arfeen, Asad; Fatima, Tasbiha
Summary: The rise of social media‐related crimes has led to the rise of mobile forensics. Since mobile forensics and privacy preservation are conflicting fields, it is important to find a middle ground where forensics can be performed on any device without compromising the confidentiality of an individual. This paper presents a framework called "role‐based mobile forensics framework with cryptography (RBMF2C)" that can be easily implemented and protects users' privacy and does not interfere with the forensic process. A mobile forensic platform called Sher‐locked phones developed using C# is also presented in this paper that is developed following the aforementioned RBMF2C framework. This platform consists of five layers: access control, evidence gathering, data analysis, privacy, and reporting layer. The developed platform implements the RBMF2C framework on the evidence gathering, analysis, and reporting layer to protect the evidential image, evidential findings, and final report from being accessed by unauthorized users. The implementation of privacy preservation techniques as proposed by the proposed framework such as role‐based access control, keyword search, and encryption/ decryption did not hinder the performance of the developed toolkit, and suspects data privacy is also preserved to a substantial extent.